PROPORTION OF THE BODY SEA CUCUMBER Stichopus vastus Sluiter - Muhammad Raihan; Mery Sukmiwati; Rahman Karnila (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractThis study aims to determine the proportion of body parts of mattresses StichopusvastusSluiterobtained from Natuna Waters of Riau Islands. The research method was carried out descriptively by analyzing the proportion of the body parts of the mattress. The results showed that the proportion of mattress sea cucumbers consisted of 78.6% flesh and skin, 21.40% stomach contents. The yield of meat powder and sea cucumber skin was 84%, and powder contents 49%.Keywords: sea cucumber mattress, proportions